Serial Determinations of PF4 and βTG: Comparisons Between Multiple Venipunctures vs a Catheter Infusion System - Strauss, William; Cella, Guiseppe; Myers, Charles; Sasahara, Arthur A (Thrombosis and Haemostasis, 1988)
Platelet factor 4 (PF4) and beta thromboglobulin (βTG) are platelet-specific proteins which are released upon platelet aggregation and which can be accurately measured by radioimmunoassay. We devised a catheter-infusion system that enables serial determinations of these proteins.In 20 subjects (10 healthy volunteers and 10 patients with stable coronary artery disease), we compared samples collected by individual venipunctures with those simultaneously obtained by means of a simple catheter-infusion system. At least 5 samples were obtained over a period of time which was as long as 60 min, and at least 30 min. Subjects with stable coronary artery disease were selected so that they would be expected to have stable and normal PF4 and βTG levels. Thus, elevations of either PF4 or βTG would represent artifacts secondary to sampling technique.Analysis of the results demonstrated that the catheter-infusion system was equivalent to individual venipunctures for determination of PF4 and βTG . 16.8% of samples obtained via the catheter and 17.2% of those obtained by individual venipunctures were spuriously elevated.A second series of studies were performed to refine the technique further by examining the impact of infusion rate and the addition of citrate phosphate dextrose (CPD) to the infusate. Ten additional subjects had catheter systems utilized in both arms simultaneously. The addition of CPD resulted in significantly less abnormal values at slower infusion rates (1 and 2.5 cc/min). At 5 cc/min D5/w or saline alone are suitable.These investigations confirm that this simple catheter system is equivalent to individual venipunctures for determination of PF4 and βTG while avoiding patient discomfort. Also noted was the fact that a high percentage of determinations could be spuriously elevated by either technique under clinical demands. Thus, multiple determinations from the same subject are necessary to assure reproducibility.
Keywords: Platelet-specific proteins; Platelet factor 4; Beta thromboglobulin